A new perspective on non-invasive diagnosis of non- alcoholic fatty liver disease: evidence integration of inflammatory and metabolic biomarkers based on a scoping review - Liang, Huimin; Zhang, Deyuan; Wei, Na; Xi, Pengjiao; Ge, Haize; Zhang, Yan (Frontiers in Endocrinology, 2025)
BackgroundNon-alcoholic fatty liver disease (NAFLD) has become the most common chronic liver condition globally, spanning a spectrum from simple steatosis to non-alcoholic steatohepatitis (NASH) and progressive fibrosis. Inflammation and metabolic dysregulation play key roles in its pathogenesis. Accordingly, inflammatory and metabolic biomarkers have gained increasing attention as potential tools for non-invasive diagnosis and disease staging.ObjectiveThis scoping review aimed to synthesize current evidence on the diagnostic performance of inflammatory and metabolic biomarkers for NAFLD, with a focus on their potential application in early screening and disease stratification.MethodsWe systematically searched PubMed and CNKI databases for relevant peer-reviewed literature published up to August 2024. The search strategy combined MeSH terms and free-text keywords, and study selection was guided by the Population–Concept–Context (PCC) framework. Methodological quality was assessed using the Newcastle–Ottawa Scale and AHRQ criteria.ResultsFifteen eligible studies (11 case-control, 2 cohort, 1 cross-sectional, and 1 retrospective study) were included, yielding 18 candidate biomarkers. The triglyceride-glucose (TyG) index was commonly associated with early-stage NAFLD screening; cytokeratin-18 (CK18) was linked to NASH detection, while adiponectin and osteopontin (OPN) were related to liver fibrosis. Additionally, inflammatory indices such as neutrophil-to-lymphocyte ratio (NLR), monocyte-to-lymphocyte ratio (MLR), and systemic immune-inflammation index (SII) showed clinical promise due to their accessibility and low cost.ConclusionInflammatory and metabolic biomarkers provide valuable non-invasive insights into the diagnosis and staging of NAFLD. The integration of multiple biomarkers may enhance diagnostic accuracy and support stratified management strategies. However, further validation is needed to establish standardized thresholds and confirm clinical utility across diverse populations.